Effect of stabilization method on the natural convection in an inclined cavity filled with MWCNTs/water nanofluids. (December 2021) - Samadzadeh, Asma; Zeinali Heris, Saeed
Abstract: The present work has been studied to investigate the effect of stabilization method on natural convection in an inclined cavity filled with MWCNTs/ water. Two cubic enclosures with different aspect ratio and slopes are tested. Non-covalent and covalent functionalization of MWCNT have been done by using gum Arabic (GA) and the amino acid Ethylene diamine (EDA) respectively. The natural convection heat transfer coefficient decreases with incrementing the concentration of nanoparticles. However, the slope of reducing of the heat transfer coefficient in lower concentrations is small and by increasing concentration, this slope enhances. The effect of changing the Rayleigh number is lower than the effect of incrementing the concentration of CNT on the Nusselt number. By reducing the inclination angle from 90 ° to 0 °, the convection heat transfer increases for both covalent and non-covalent functionalized nanoparticles. Also, it was found that changing the inclination angle does not affect the Nusselt number at the low Rayleigh numbers. With incrementing the Rayleigh number and changing the inclination angle, changing of the heat transfer coefficient at Ar = 2 was more than Ar = 1. The free convection heat transfer coefficient of the non-covalent method had more reduction in comparison to the covalent method.